Investigation on In–TiO2 composites as highly efficient elecctrocatalyst for CO2 reduction. (20th April 2020) - Wang, Xikui; Jiang, Xingxing; Wang, Qinglong; Zhang, Tao; Li, Peize; Wang, Mingkui; Shen, Yan
Abstract: Electrochemical CO2 reduction (ECR) to produce value added chemicals such as formic acid in aqueous solutions has gained significant attention to alleviate the increasing demand of industrial supplies in past two decades. The metal In, featuring with d 10 orbit properties, holds a high potential to be efficient catalyst for ECR. Related literatures have reported that In is a promising electrocatalyst to generate formic acid. However, it's Faraday efficiency of producing formic acid is relatively low owing to a finite catalytic activity. Herein, we report an effective approach of introducing TiO2 as the substrate of In catalyst to activate and stabilize the CO2 − intermediates. The in-situ CO2 − ultraviolet absorption spectrum test and scanning electrochemical microscope fully confirm that the ability of In catalyst to reduce CO2 by one-electron can be extremely enhanced after introducing TiO2 substrate. More importantly, the resultant In–TiO2 catalyst for ECR to produce HCOOH has achieved an augmented catalytic activity with a high Faraday efficiency of 86% at −1.6 V (vs. SCE), which is obviously higher than that of In (58%) catalyst. Detailed investigation has revealed that the Ti 3+ sites formed by self-doping on the surface of TiO2 substrate are contributed to the one-electron reduction of CO2 molecules to CO2 − intermediates and the formation of Ohmic contact in the In–TiO2 composites could promote the efficient conversion of CO2 − intermediates to HCOOH products. Graphical abstract: Image 1 Highlights: A In–TiO2 composite catalyst used to heterogeneous system be designed and composited. The catalyst exhibits high Faraday efficiency for electrochemical CO2 reduction to formic acid. The CO2- intermediates be found by In-situ ultraviolet absorption spectrum test. This work provides a new design idea of composite catalyst with Ohmic contact.